Equilibrium of truss and beam structures of inelastic materials - Hagsten, Lars German (Journal of Civil Engineering and Management, 2017)
A physically based method for the determination of equilibrium for structures with inelastic response is described. The method is based on minimisation of the potential energy. For structures with inelastic response, some of the applied energy is converted to non-mechanical energy. This part of the energy is dissipated. According to the conservation of energy the dissipated energy must simultaneously be subtracted the mechanical energy in order to determine the change of the potential energy. Changes of the strains in the structure, from non-static conditions, such as thermal deformations and shrinkage, as well as plastic strains from previous load scenarios, will also change the potential energy. The method is also capable of taken these effects into account. Three examples are included in order to support the physical understanding, and to illustrate the procedure for the application of the method. Information regarding the necessary ductility of the individual parts forming the complete structure is achieved as outcome of the analysis.First published online: 22 Feb 2017